Boosting Solid‐State Diffusivity and Conductivity in Lithium Superionic Argyrodites by Halide Substitution. (23rd May 2019) - Adeli, Parvin; Bazak, J. David; Park, Kern Ho; Kochetkov, Ivan; Huq, Ashfia; Goward, Gillian R.; Nazar, Linda F.
Abstract: Developing high‐performance all‐solid‐state batteries is contingent on finding solid electrolyte materials with high ionic conductivity and ductility. Here we report new halide‐rich solid solution phases in the argyrodite Li6 PS5 Cl family, Li6− x PS5− x Cl1+ x, and combine electrochemical impedance spectroscopy, neutron diffraction, and 7 Li NMR MAS and PFG spectroscopy to show that increasing the Cl − /S 2− ratio has a systematic, and remarkable impact on Li‐ion diffusivity in the lattice. The phase at the limit of the solid solution regime, Li5.5 PS4.5 Cl1.5, exhibits a cold‐pressed conductivity of 9.4±0.1 mS cm −1 at 298 K (and 12.0±0.2 mS cm −1 on sintering)—almost four‐fold greater than Li6 PS5 Cl under identical processing conditions and comparable to metastable superionic Li7 P3 S11 . Weakened interactions between the mobile Li‐ions and surrounding framework anions incurred by substitution of divalent S 2− for monovalent Cl − play a major role in enhancing Li + ‐ion diffusivity, along with increased site disorder and a higher lithium vacancy population. Abstract : Die Grenze des Mischkristall‐Regimes : Li5.5 PS4.5 Cl1.5 zeigt eine hohe Li + ‐Ionenleitfähigkeit von 9.4 mS cm −1 bei 298 K mit einer Aktivierungsenergie von 0.29 eV und einen hohen Li + ‐Diffusionskoeffizienten von 1.01×10 −11 m 2 s −1, der durch NMR‐Transportmessungen bestimmt wurde. Dies weist auf eine hervorragende Eignung als Festkörper‐Li‐Ionen‐Elektrolyt hin.